22nd Annual IEEE Symposium on Logic in Computer Science (LICS 2007) 2007
DOI: 10.1109/lics.2007.9
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Class of Context-Sensitive Languages

Abstract: We define a new class of languages defined by multi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
174
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(175 citation statements)
references
References 22 publications
1
174
0
Order By: Relevance
“…Before we introduce our new automata model, we recall multi-stack visibly pushdown automata, as recently introduced by La Torre, Madhusudan, and Parlato [16]. Though this model will be parametrized by Σ, it is not distributed yet.…”
Section: Concurrentmentioning
confidence: 99%
See 3 more Smart Citations
“…Before we introduce our new automata model, we recall multi-stack visibly pushdown automata, as recently introduced by La Torre, Madhusudan, and Parlato [16]. Though this model will be parametrized by Σ, it is not distributed yet.…”
Section: Concurrentmentioning
confidence: 99%
“…Moreover, it was shown that Mvpa can in general not be complemented [5]. We can remedy this situation by restricting our domain to k-phase words [16]. Let k ∈ N. A word w ∈ Σ * is called a k-phase word over Σ if it can be written as…”
Section: Concurrentmentioning
confidence: 99%
See 2 more Smart Citations
“…In [TMP07], La Torre et al propose a more general definition of the notion of a context. For that, they define the class of bounded-phase visibly multi-stack pushdown automata (BVMPA) where only those runs are taken into consideration that can be split into a given number of phases, where each phase admits pop transitions of one particular stack only.…”
Section: Introductionmentioning
confidence: 99%